Relação entre modernidade organizacional e comprometimento organizacional: um estudo nas sociedades de economia mista do governo do Estado do Ceará - Arraes, Vanessa Machado (2014)
The goal of this research is to investigate the relationship between organizational modernity and organizational commitment from the perspective of public employees of the Joint Stock Companies of the Government of the State of Ceará. The study also examines the situation of the variables involved in theoretical models, supported in addressing organizational modernity standards, proposed by Eboli (1996) as validated by Sant'Anna (2002), and three-dimensional approach of organizational commitment proposed by Meyer Allen and Smith (1993), validated in Brazil by Medeiros and Enders (1998). The research is quantitative and descriptive and the field data were collected through a questionnaire. Data were analyzed statistically involving descriptive techniques and multivariate analyzes. The research population consisted of 479 public employees and a sample of 339 respondents, which, after the removal of outliers, summed up to 324 respondents. The achievements contemplated the evaluation of the psychometric properties of the organizational modernity scales and organizational commitment, through exploratory and confirmatory factor analysis, which permitted the exclusion of indicators of the two scales and the redenomination of modernity dimensions. A general evaluation, modernity organizations was classified as moderate. The affective commitment and normative were assessed as high, and the instrumental as moderate. It was found also by structural equation modeling a positive and significant relationship between modernity and organizational affective commitment and normative, the same was not true for the instrumental commitment.